Hematobiochemical Effects of Telakucha (Coccinia Indica) in Alloxan Induced Diabetic Rats (Research in Agriculture Livestock and Fisheries, 2020)
The study was undertaken to investigate the effects of Telakucha (Cocciniaindica) on blood glucose, serum total cholesterol, hematological parameters and body weight in alloxan induced diabetic rats. In this experiment 45 rats were selected for the trial purpose. The rats were divided into 3 equal groups, each containing 15 individuals (n=15) as follows: normal control (C) group, diabetic control (DC) group and diabetic treatment (DT) group. Diabetes was induced in diabetic control (DC) and diabetic treatment (DT) group with alloxan @ 200mg/kg body weight intraperitonially. Then diabetic treatment group (DT) was treated with 10% aqueous extract of Telakucha @500 mg/kg body weight. After 42 days of treatment, Telakucha extract reduced the amount of blood glucose significantly (P